Survey of diagnostic and treatment practices for multiple sclerosis (MS) in Europe. Part 2: Progressive MS, paediatric MS, pregnancy and general management. (28th February 2018) - Fernández, O.; Delvecchio, M.; Edan, G.; Fredrikson, S.; Giovannoni, G.; Hartung, H.‐P.; Havrdova, E.; Kappos, L.; Pozzilli, C.; Soerensen, P. S.; Tackenberg, B.; Vermersch, P.; et al.
Abstract : Background and purpose: The European Charcot Foundation supported the development of a set of surveys to understand current practice patterns for the diagnosis and management of multiple sclerosis (MS) in Europe. Part 2 of the report summarizes survey results related to secondary progressive MS (SPMS), primary progressive MS (PPMS), pregnancy, paediatric MS and overall patient management. Methods: A steering committee of MS neurologists developed case‐ and practice‐based questions for two sequential surveys distributed to MS neurologists throughout Europe. Results: Respondents generally favoured changing rather than stopping disease‐modifying treatment (DMT) in patients transitioning from relapsing−remitting MS to SPMS, particularly with active disease. Respondents would not initiate DMT in patients with typical PPMS symptoms, although the presence of ≥1 spinal cord or brain gadolinium‐enhancing lesion might affect that decision. For patients considering pregnancy, respondents were equally divided on whether to stop treatment before or after conception. Respondents strongly favoured starting DMT in paediatric MS with active disease; recommended treatments included interferon, glatiramer acetate and, in John Cunningham virus negative patients, natalizumab. Additional results regarding practice‐based questions and management are summarized. Conclusions: Results of part 2 of the survey of diagnostic and treatment practices for MS in Europe largely mirror results for part 1, with neurologists in general agreement about the treatment and management of SPMS, PPMS, pregnancy and paediatric MS as well as the general management of MS. However, there are also many areas of disagreement, indicating the need for evidence‐based recommendations and/or guidelines.